2018
DOI: 10.31080/asmi.2018.01.0010
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Carriage of Staphylococcus aureus and Associated Risk Factors among Students in a Nigerian University

Abstract: Staphylococcus aureus, one of the most frequently occurring community and hospital-associated pathogens, causes infectious diseases including mild skin infection to systemic infections [1].Approximately 20 -30% of the global population is persistently colonized with S. aureus in the anterior nares [2] and approximately 10 to 40% of people tested as outpatients or on admission are nasal carriers of S. aureus [3]. Nasal carriage (colonization) of S. aureus has been identified as a major risk factor for subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…The overall prevalence of nasal S. aureus colonization in this study is 66.6%. This is higher than previous reports of 32.9% [6]; 14.0%; 56.3% [7] and 56.7% [8]. It is however lower than 80% [9].…”
Section: Discussioncontrasting
confidence: 77%
“…The overall prevalence of nasal S. aureus colonization in this study is 66.6%. This is higher than previous reports of 32.9% [6]; 14.0%; 56.3% [7] and 56.7% [8]. It is however lower than 80% [9].…”
Section: Discussioncontrasting
confidence: 77%
“…The prevalence rate observed is significantly higher than the previous reports of 80% isolation of S. aureus by Chigbu and Ezeronye [19], and 32.4% and 39% reported by Kuehnert (2006) and Abdulhadi [20] respectively. A higher carriage rate was observed in male students which is in line with the study that reported a significant difference between sex for carriage rate [21], but no significant difference at p=0.05 between the male and female was observed in this study. Nevertheless, Odu and Okonko, [4], report higher carriage rate in female, this further support the report of Adesida et al, ( 2007) that gender has no significant effect on carriage rate.…”
Section: Discussionsupporting
confidence: 91%
“…Ayepola et al demonstrated that hospitalization in the previous 12 months, male gender, S. aureus skin infections and participation in sports were significant risk factors for colonization in Nigerian university students ( 63 ).…”
Section: Risk Factors For S Aureus Colonizationmentioning
confidence: 99%